Farm Women’s willingness to pay for bio fortified rice variety-a micro level study - Waris, Amtul; Neeraja, CN; Azam, M Mohibbe (ORYZA-An International Journal of Rice, 2019)
Milled rice, though a good source of energy, is poor source of micronutrients. Where rice is a staple food,Â fortification with essential vitamins and minerals would make it more nutritious, which can fetch premium price.Â This study used the contingent valuation method (CVM) to estimate the farm women’s willingness to pay (WTP)Â for DRR Dhan 45, the bio-fortified (with zinc) rice variety developed by ICAR-Indian Institute of Rice Research,Â Hyderabad. Correlation analysis was carried out to ascertain the significant relationships of WTP withÂ socioeconomic variables. The farm women were willing to pay an average premium of about 26% over theÂ prevailing price of non-bio-fortified rice. The results also showed that young and educated farm women areÂ willing to pay higher price, who in turn could be the potential target group for creating awareness andÂ promotion of bio-fortified rice varieties to address the micronutrient deficiencies among malnourished masses.